REALISASI AFEK PADA TALK SHOW MATA NAJWA ON STAGE “SEMUA KARENA AHOK” - Khaofia, Suci (Adabiyyāt: Jurnal Bahasa dan Sastra, 2018)
This research discusses the realization of affect as a part of interpersonal meaning in a talk show of Mata Najwa on stage “Semua Karena Ahok”. The research is a descriptive qualitative research. The source of data in this research is the dialogue of Najwa Shihab which contains polarity and lexis attitudinal. The result shows that Mata Najwa on stage “Semua Karena Ahok” has three patterns of polarity and lexis appears in talk show; 1) positive polarity with positive attitudinal lexis, means positive, 2) positive polarity with negative attitudinal lexis, means negative and 3) negative polarity with negative attitudinal lexis, means negative. Najwa Shihab expresses positive attitude to Ahok but neutral to other participants. Najwa Shihab also express both positive and negative to the topic of the dialogue such as Jakarta, Mata Najwa on Stage, and traffic in Jakarta.